Nilai Guna dan Nilai Tukar dalam Mekanisme Pasar: Studi Komparatif Pemikiran Ibnu Khaldun dan Adam Smith - Lina Azizah; M. Riza Wahyu Alhadi Abror (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to examine the concepts of use value and exchange value in market mechanisms through a comparative study of the thoughts of Ibn Khaldun and Adam Smith. This study is a qualitative literature review. The primary data sources consist of the original works of Ibn Khaldun and Adam Smith, while the secondary data sources include relevant books and scientific articles. Data collection techniques were carried out through literature classification and documentation, while data analysis used content analysis and comparative analysis. The results of the study show that Ibn Khaldun views use value as a function of the utility of goods that is limited and does not directly determine exchange value. In contrast, Adam Smith placed use value as a conceptual instrument to explain the paradox of value, while exchange value was represented through market prices and labor contributions. Both figures agreed that use value was obtained through consumption activities and was not influenced by price levels, but rather by the inherent function of goods. However, differences arose in the standards for measuring exchange value and in the conceptual characteristics of use value put forward by each figure.